Pendampingan Penyusunan Laporan Keuangan Koperasi Abi Makmur Bersama - Nurharibnu Wibisono; Fatchur Rochman (Universitas Merdeka Madiun, 2021)
This activity service purposes to provide accounting counseling for cooperatives as well as assistance activities in preparing financial reports at the ABI Makmur Bersama Cooperative in accordance with applicable regulations. This community service method is counseling on accounting materials and assistance in preparing financial reports. The target participants are the ABI Makmur Bersama Cooperative Management. The time for the activity is November 2019 - January 2020. This activity took place at the ABI Makmur Bersama Cooperative, Jalan Manggala Mulya number 65, Rejomulyo Village, Kartoharjo District, Madiun City. After conducting counseling and mentoring, cooperative management 1) understands cooperative accounting and the principles of its preparation. 2) Cooperative management, especially treasurer, can make a cooperative financial report. 3) Cooperative management is able to report the cooperative's financial performance in terms of inventory and sales development.